Spin polarized Fe1−Ti pairs for highly efficient electroreduction nitrate to ammonia - Dai, Jie; Tong, Yawen; Zhao, Long; Hu, Zhiwei; Chen, Chien-Te; Kuo, Chang-Yang; Zhan, Guangming; Wang, Jiaxian; Zou, Xingyue; Zheng, Qian; Hou, Wei; Wang, Ruizhao; et al. (Nature communications, 2024)
Electrochemical nitrate reduction to ammonia offers an attractive solution to environmental sustainability and clean energy production but suffers from the sluggish *NO hydrogenation with the spin–state transitions. Herein, we report that the manipulation of oxygen vacancies can contrive spin−polarized Fe 1 −Ti pairs on monolithic titanium electrode that exhibits an attractive NH 3 yield rate of 272,000 μg h −1 mg Fe −1 and a high NH 3 Faradic efficiency of 95.2% at −0.4 V vs. RHE, far superior to the counterpart with spin−depressed Fe 1 −Ti pairs (51000 μg h –1 mg Fe –1 ) and the mostly reported electrocatalysts. The unpaired spin electrons of Fe and Ti atoms can effectively interact with the key intermediates, facilitating the *NO hydrogenation. Coupling a flow−through electrolyzer with a membrane-based NH 3 recovery unit, the simultaneous nitrate reduction and NH 3 recovery was realized. This work offers a pioneering strategy for manipulating spin polarization of electrocatalysts within pair sites for nitrate wastewater treatment. Electrochemical nitrate reduction to ammonia offers an attractive solution to environmental sustainability and clean energy production. Here, the authors construct spin−polarized Fe 1 −Ti pairs via manipulating oxygen vacancies on monolithic titanium electrode for highly efficient nitrate to ammonia conversion.